2019
DOI: 10.1055/s-0038-1677551
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Co-occurrence of Intestinal Malrotation and Hirschsprung's Disease in a Neonate with 13q21.31q33.1 Interstitial Deletion Including the EDNRB Gene

Abstract: We report a rare co-occurrence of intestinal malrotation and Hirschsprung's disease (HSCR) in a male neonate with a large 38.8 Mb interstitial deletion of chromosome 13 extending from q21.31 to q33.1 including the EDNRB gene, who presented with craniofacial dysmorphic features and central nervous system malformations. The loss of EDNRB gene in addition to bilateral hearing loss and HSCR suggested an additional diagnosis of Waardenburg–Shah's syndrome. This case highlights the fact that prior knowledge of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Three cases in our study did not have postnatal diagnostic evaluation, by which duodenal atresia could be confirmed. Combined with the three cases of this study and previous studies, 24,26,33‐35 these results identify a further expansion of the prenatal presentation of 13q deletion.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Three cases in our study did not have postnatal diagnostic evaluation, by which duodenal atresia could be confirmed. Combined with the three cases of this study and previous studies, 24,26,33‐35 these results identify a further expansion of the prenatal presentation of 13q deletion.…”
Section: Discussionsupporting
confidence: 84%
“…One study has suggested abnormalities in neural crest cell migration, in conjunction with vascular disruption, as possible pathogenic mechanisms of duodenal atresia 24 . The co‐occurrence of HD and intestinal obstruction, in association with a partial deletion of chromosome 13q, has been described in previous case reports 24,33‐35 . Three cases in our study did not have postnatal diagnostic evaluation, by which duodenal atresia could be confirmed.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Previous reports suggested that eye malformation might be associated with the EFNB2 gene [4], and deletion of the 13q32 region [2]. Recently, the 13q33.3-q34 deletion (110,302,002-11,394,979, GPCh37) has been shown to be associated with microphthalmia or anophthalmia with/without coloboma in 15 patients [16], and 13 genes were encoded in the region: IRS2 GPC5 ZIC2 EFNB2 finger anomaly [5,11] Phenotype of the present patient VACTER/VACTEL association [6][7][8]10] hearing loss [23][24][25] Dandy Walker malformation [4,[12][13][14][15] Candidate genes [113862507-113921422] (GpCh37) [7]. In our review of these genes, IRS2 was reported to be involved in retina function [17,18].…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported that EFNB2 haploinsufficiency [23][24][25] or 13q32 deletion [15], is involved in hearing loss, although deafness has been reported in the patients with deletions of the 13q13.1-q14.3 and 13q12.3-q21.1 [26]. Furthermore, EFNB2 is involved in the morphogenesis of the endolymphatic sac and duct epithelia in the mouse inner ear, which requires normal hearing [27].…”
Section: Discussionmentioning
confidence: 99%